Pengaruh Brand Image, Social Media Marketing, Product Quality, Content Marketing Dan Fear Of Missing Out Terhadap Purchase Intention - Zelina Sofa Purnama; Sarah Dien Hawa (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2026)
This study aims to investigate the influence of brand image, social media marketing, product quality, content marketing, and fear of missing out on purchase intention at the MSMEs Kopi Majana 575. The research is motivated by declining sales reflecting weak purchase intention. Using a quantitative approach with non-probability sampling and purposive sampling technique, this study collected data from 122 respondents and analyzed it using PLS-SEM via SmartPLS. The results show that brand image and product quality have a significantly positively influence purchase intention, while social media marketing and fear of missing out have no significant effect on purchase intention. However, content marketing has a significant negative impact on purchase intention. These findings provide strategic insights for Kopi Majana 575 MSME to inhance purchase intention by strengthening brand image and improving product quality, as well as laveraging emotional approaches based on trends to build emotional connections with consumers.